Guru Sebagai Motivator untuk Mengembangkan Minat Belajar Siswa terhadap Matematika - Silalahi, R. Indah; Dirgantoro, Kurnia Putri Sepdikasari (SUKMA: Jurnal Pendidikan, 2023)
One of the most typical problems experienced during the learning process for mathematics is the lack of student motivation in their studies. To assist students in resolving this problem, the teacher's position as a motivator is essential. It is hoped that the teacher's passion will increase the student's interest in studying, resulting in a successful learning process. This study asks the following question: How can a teacher pique a student's interest in mathematics? The purpose of this study is to examine the significance of the teacher's role as a motivator in promoting students' excitement for learning. Techniques for qualitative research were used to write this essay. The study's subject population consisted of 39 students in grades IX-A and IX-C. Reaching learning goals is hampered by learning problems. For students to achieve these goals, the teacher must be able to motivate them. The findings of this study show that a teacher's role as a motivator can correspond to the indicators of learning mathematics interest. To make it clear how the instructor's position affects students' motivation for learning, the author suggests utilizing the teacher as a motivator more than twice.